Co-stimulation by TLR7/8 ligand R848 modulates IFN-γ production of porcine γδ T cells in a microenvironment-dependent manner. (January 2023) - Bettin, Leonie; Darbellay, Joseph; van Kessel, Jill; Buchanan, Rachelle; Popowych, Yurij; Gerdts, Volker
Abstract: Gamma-Delta (γδ) T cells represent a prominent lymphocyte subset in pigs. Their role and function, however, remains largely unknown. Toll-like receptors (TLR) are key receptors for the recognition of pathogens, but so far, it is unknown if porcine γδ T cells express TLRs and therefore have the innate ability to recognize pathogens through pattern recognition receptors. In this study, we compared γδ T cells in different age groups of pigs and investigated the functional relevance of TLR7/8 expression. We found that the major γδ T cell phenotype shifts from CD2 − CD8α −/dim CD27 + in young pigs to CD2 + CD8α high CD27 − in 3-year-old pigs impacting their ability to produce IFN-γ upon cytokine and TLR stimulation. Furthermore, we report that stimulation with TLR7/8 ligand R848 increased IFN-γ production in purified γδ T cells upon co-stimulation with IL-2 and IL-12. However, the effect of R848 as a co-activator of γδ T cells was abrogated by the addition of monocytes or within PBMCs, suggesting that γδ T cells respond to multiple direct and indirect stimulations. Thus, our results indicate that γδ T cells express TLRs, are modulated by TLR7/8 ligand R848 and have subset-specific responses. Highlights: Porcine γδ T cells showed age-dependent differences in their phenotypes. γδ T cells express Toll-like receptors and show the highest expression for TLR7. TLR 7/8 ligand R848 is a potent co-activator of purified γδ T cells. IFN-γ is mainly produced by CD2 + Ki67 + CD25 + γδ T cells in purified cultures. The cross-talk with other cells modulated the co-stimulatory effect of R848 on γδ T cells.